Product Modelling for AAC/CAPP Integration - Pobożniak, Janusz (Communications - Scientific letters of the University of Zilina, 2000)
The key condition for achieving the full automation is the integration of CAD/CAPP/CAM systems. The important element in the development of computer aided production preparation system is product modelling. The most widely known modelling method is feature based modelling. The mentioned method is very promising because it can extensively use the geometric model created in CA system. The enhancement of product information exchange between systems working in CE environment can increase the level of computer automation. The proposed system architecture fulfilling the requirements is presented in the article.